Evaluation of the possible role of ants (Hymenoptera: Formicidae) as mechanical vectors of nematodes and protists - Villani, Fabio; Morini, Maria Santina de Castro; Franco, Marco Antonio; Bueno, Odair Correa [UNESP] (Brazilian Archives of Biology and Technology, 2008)
Os Nematoda e Protista podem ser transmitidos ao homem de diversas maneiras, mas pouca ênfase é dada para a transmissão mecânica por intermédio de formigas. Assim, esse trabalho procurou investigar a transmissão mecânica de ovos de Ascaris lumbricoides e cistos de Entamoeba coli pelos Formicidae. Através de experimentos com espécies mantidas em ninhos no laboratório (Tapinoma melanocephalum, Linepithema humile e Monomorium pharaonis) e com 17 espécies de formigas de uma área antropizada na região de Mogi as Cruzes (SP), foi possível constar que os ovos A. lumbricoides foram transportados por L. humile, tanto no campo (1 operária) como no laboratório (1 operária), por Camponotus rufipes (2), por Solenopsis saevissima (1) e por Acromyrmrex niger (1). em três operárias de C. rufipes foram encontrados cistos de E. coli. Apesar da baixa incidência de transporte, as três primeiras espécies pelo fato de viverem muito próximas ao ser humano, podem levar para dentro do ambiente domiciliar patógenos de Nematoda e Protista.

Nematodes and protists can be transmitted to humans in many ways and little concern has been given to the mechanical transmission by ants. This study aimed at analysing how the eggs of Ascaris lumbricoides and cysts of Entamoeba coli could be mechanically transmitted to the man by Formicidae. Through the experiments using nests of Tapinoma melanocephalum, Linepithema humile and Monomorium pharaonis reared in the laboratory allied to observations of some 17 ant species in an urban park area in Mogi das Cruzes (SP), it was found that L. humile was capable of carrying eggs of A. lumbricoides both in the field and laboratory conditions (1 worker), as well as was Camponotus rufipes (2), Solenopsis saevissima (1) and Acromyrmex niger (1). The cysts of Escherichia coli were found over three workers of C. rufipes. Although the frequency of the workers found transporting pathogens was low, the capacity of common household species in carrying pathogens like nematodes and protists was demonstrated.
Keywords: Ascaris lumbricoides; Entamoeba coli; ant; mechanical vector